O imaginário sertanejo no Romance d‘A Pedra do Reino e o príncipe do sangue do vai-e-volta: memória e invenção em uma imagística quadernesca - Narvaes, Giuliarde de Abreu [UNESP] (2014)
The imaginary is characterized, among other acceptations, as a set of mental productions that turns into artworks. The visual and linguistic images from the our imaginary are responsible for assigning coherence and dynamism to set. In this research we study the fictional imaginary in Romance d’A Pedra do Reino e o príncipe do sangue do vai-e-volta, written by Ariano Suassuna a brazilian writer from Paraíba. In his creation it´s possible to note the fruitful communion between the images that comes sometimes from the popular roots of northeastern culture, sometimes from a diversity of other works belonging to the canon of western classical culture. Novelist, poet, and creator of a new northeastern dramaturgy, Ariano Suassuna was also creator of the Armorial Movement, that started in Recife, in 1970. So we believe this movement results in a unique cultural project, engaged with the matchup of different arts, so relate the popular and erudite production. On route that we undertake through this Suassuna creation, we highlight the Romance d’A Pedra do Reino, first of all, as a narrative compendium of Armorial ideas, and this prerogative has become one of our itineraries in the critical crossing along this novel. In this work, we propose to think what it is and how it is the imaginary in the context of a fictional work, specifically we also realizing the presence of the narrator as an imaginative consciousness able to determine the form and substance to the images collected in its imaginative action (narration). So, with the study of erudite, popular, individual and collective memories, we mobilized the composition of a backlander imaginary. We also observed, in Romance d’A Pedra do Reino´s context, the fusion and a figuratively aesthetics from different sources memorials. They are like a fundamental substrate necessary to the Novel composition. We highlight, at the end of the research, compiling an erudite and popular tradition in ...